Information Inertia - ILLEDITSCH, PHILIPP K.; GANGULI, JAYANT V.; CONDIE, SCOTT (Journal of Finance, 2021)
ABSTRACT We show that aversion to risk and ambiguity leads to information inertia when investors process public news about assets. Optimal portfolios do not always depend on news that is worse than expected; hence, the equilibrium stock price does not reflect this bad news. This informational inefficiency is more severe when there is more risk and ambiguity but disappears when investors are risk‐neutral or the news is about idiosyncratic risk. Information inertia leads to news momentum (e.g., after earnings announcements) and is consistent with low household trading activity. An ambiguity premium helps explain the macro and earnings announcement premium.